The Sleep Quality of the Frontline Healthcare Workers and the Improving Effect of Tai Chi - Zhan, Jingye; Yang, Kangdi; Sun, Zhuoer; Bai, Lingling; Lu, Xiaoying; Wang, Xiuhong; Liu, Weizhi; Yi, Chen; Wang, Lina (Frontiers in Psychiatry, 2022)
Background: A number of studies have documented that COVID-19 brought more negative impact on the physical and psychological functioning of front-line healthcare workers. Especially, sleep quality was focused. The present study aimed to investigate the sleep quality of front-line healthcare workers, risk factors for sleep quality and the effect of Tai Chi training. Methods: 98 front-line healthcare workers were recruited, coming from the infection department, fever clinic, laboratory and medical imaging department in a COVID-19 designated hospital in Shanghai. 50 of them participated in a 2-week intervention and were randomized to receive a Tai Chi training or relaxation training. Participants were assessed at baseline, 7 and 14 days after participation. Demographic information, sleep quality and anxiety were measured by using the demographic questionnaire, Pittsburgh Sleep Quality Index (PSQI) and Beck Anxiety Inventory (BAI). Results: 13.3% participants were above the cut-off score (>10) for the PSQI. Regression analysis showed gender, age, working years and job category had effect on sleep quality. And compared to control group, participants in Tai Chi training group had lower scores on both PSQI (p<0.05) and BAI (p<0.01) after the 2-week intervention. Conclusion: It was demonstrated that poor sleep quality existed in the front-line healthcare workers, which was related to gender, age, working years and job category. Tai Chi training can dramatically improve their sleep quality and reducing anxiety symptoms.